IMPLEMENTASI PRESSURE TRANSMITTER SEBAGAI PENGUKUR TEKANAN PADA MODUL ICE CUBE MAKER UNTUK PRAKTIKUM SISTEM REFRIGERASI - Sunardi Sunardi; Muhammad Nuriyadi; Widya Yeni Rawati; Warsono Warsono (JURNAL SIMETRIK, 2026)
Pressure measurement is a crucial parameter in refrigeration systems, serving as a primary indicator of system condition and performance. Pressure data not only reflects compressor workload but also enables the calculation of the Coefficient of Performance (COP) as a benchmark of system efficiency. However, the existing ice cube maker practicum module is not equipped with pressure measurement instruments, limiting practical analysis to visual observation and temperature measurement only. This study integrates a pressure transmitter into the ice cube maker module to provide accurate pressure data. Experimental results show that pressure measurements using the pressure transmitter are more precise and responsive to pressure variations, useful for detecting pressure surges, and capable of providing more accurate and detailed data on refrigeration system performance. Digital measurements yielded an average system operating power of 663.4 Watts with a deviation of 2.85%, while manual measurements produced an average power of 660 Watts with a deviation of 3.43%. Furthermore, digital measurements better represent the actual system operating conditions, resulting in a Coefficient of Performance (COP) of 3.13 with a deviation of 4.1%. Keywords: Pressure transmitter, Pressure Gauge, Refrigeration System